PROFILE OF ACCIDENTS AT WORK WITH NEGLIGENCE PRODUCTS NEEDLESTICK GROUP "E" (Fiep Bulletin - online, 2016)
Sharps injuries in the group "E" are highly complex, since several contaminations could provide biological risks, highlighting the acquired immune deficiency syndrome (AIDS), hepatitis B and C among others. The aim of this study was to determine the profile of workplace accidents for negligence and recklessness with sharps group "E" in a hospital in Foz do Iguaçu, state of Paraná, Brazil. Data collection was through records of accidents reported in the period January to December 2013. The statistical method used was descriptive and exploratory analyzed by Bioestatic 5.0 and Excel for Windows. Regarding the time of accident data presented in the afternoon (38%), night (31%), whole period (10%), and morning (21%); as was the type, for disposal of this material (26%), venipuncture (26%) surgical procedures (15%), others (28%) and drug administration (5%); regarding the use of personal protective equipment (PPE) (56%) were with PPE at the time of the accident, and (44%) did not. It is concluded that the accident happened, both negligent and recklessly.
Keywords: sharps; negligence; recklessness